Ultra‐Fast and Scalable Saline Immersion Strategy Enabling Uniform Zn Nucleation and Deposition for High‐Performance Zn‐Ion Batteries. Issue 33 (6th July 2021) - Xu, Xilian; Chen, Ye; Zheng, Dong; Ruan, Pengchao; Cai, Yanhui; Dai, Xiaojing; Niu, Xinxin; Pei, Chengjie; Shi, Wenhui; Liu, Wenxian; Wu, Fangfang; Pan, Zhiyan; et al.
Abstract: Although aqueous Zn‐ion batteries (ZIBs) with low cost and high safety show great potential in large‐scale energy storage system, metallic Zn anode still suffers from unsatisfactory cycle stability due to unregulated growth of Zn dendrites, corrosion, and formation of various side products during electrochemical reaction. Here, an ultrafast and simple method to achieve a stable Zn anode is developed. By simply immersing a Zn plate into an aqueous solution of CuSO4 for only 10–60 s, a uniform and robust protective layer (Zn4 SO4 (OH)6 ·5H2 O/Cu2 O) is formed on commercial Zn plate (Zn/ZCO), which enables uniform electric field distribution and controllable dendrite growth, leading to a long‐term cycle life of over 1400 h and high average Coulombic efficiency (CE) of 99.2% at 2.0 mA cm −2 and 2.0 mAh cm −2 . These excellent characteristics of the prepared Zn anode show great potential in practical applications for high‐performance aqueous Zn‐ion batteries. Abstract : An ultrafast, low‐cost, and scalable saline immersion method is proposed to achieve Zn anodes with outstanding stability over 1400 h with low nucleation overpotential of 28.9 mV, and high average CE of 99.2 % with low voltage gap of 47.3 mV over 450 cycles, exhibiting promise for high‐performance aqueous Zn‐ion batteries.